A Comparison Effect Of feeding Barley or Soybean Meal Chemically Treated As A Source Of Undegradable Protein in Milk Production and Composition in Awassi Ewes - Mohammed, Omar Dheyaa; Abdullah, Mohammed Najim; Abbo, Nadir Yousef; Salih, Nashwan Nather (Journal of agricultural, environmental and veterinary sciences, 2020)
This study was conducted in animal research department at Ministry of Agriculture , by using 21 Awassi ewes with single lambs , after two weeks of birth , the average body weight 60.90 ± 1.92 kg and ages 3- 5 years. The ewes were divided into three groups , which was fed ad libitum on the experimental rations , first group (T1) was fed on control ration consist of barley grain , wheat bran , soybean meal and wheat straw which contained 13.46% crud protein , second (T2) and third (T3) group were fed on ration consist neither slow degradable barley grain nor slow degradable soybean meal as a source of undegradable protein and contained 16% crud protein , All ration was iso calorie and iso degradable protein. Results was indicated to a significant (p
Keywords: undegradable protein; milk yield; ewes